Empowering the Lembah Subur Morome Farmer–Livestock Group through Forage Planting Training in Konda District, South Konawe Regency - Yaddi, Yamin; Munadi, La Ode Muh.; Aku, Achmad Selamet; Jabuddin, La Ode; Pagala, Muhammad Amrullah; Zulakrnain, Deki; Astarika, Rina; Purwanti, Bea (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
The community service program aims to enhance the knowledge and skills of farmer-livestock groups in managing livestock feed. Its main objective is to improve the capacity of farmers in forage production to ensure a consistent supply of livestock feed, particularly during the dry season. The training focused on the selection, cultivation, and maintenance of forage species such as Pennisetum purpureum (elephant grass). Post-training evaluations showed a significant improvement in participants' knowledge and skills, particularly in understanding forage planting techniques. Additionally, the program successfully increased the availability of livestock feed, reduced dependence on external feed sources, and stabilized livestock productivity. The results of this community service align with the theory of empowerment through skill-based agricultural training and sustainable farming practices, as well as findings from previous studies on the impact of forage planting on livestock production. This program concludes. This program concludes that training and technical assistance for farmers are essential in ensuring food security and improving economic independence.